2012
DOI: 10.1111/j.1440-1754.2010.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis in children

Abstract: Allergic rhinitis affects up to 40% of children but is commonly undiagnosed. Careful assessment of nasal symptoms allows for the most appropriate therapeutic options to be chosen. Allergen avoidance is often difficult in practice. Antihistamines are of limited benefit in allergic rhinitis caused by house dust mite and other perennial allergens, where symptoms, predominantly nasal obstruction, are not histamine mediated. In contrast, symptoms triggered by pollen, such as nasal itch, rhinorrhoea and sneezing, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 46 publications
1
30
1
7
Order By: Relevance
“…On the contrary, perennial rhinitis with the prominent symptom of nasal blockage is more common in primary and preschool age children and allergens usually implicated include the house dust mite (HDM) (e.g. Dermatophagoides pteronyssinus and Dermatophagoides farinaeae) and animal dander [4]. The pattern of rhinitis (seasonal or perennial) also depends by the climatic environment (temperate or tropical) [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, perennial rhinitis with the prominent symptom of nasal blockage is more common in primary and preschool age children and allergens usually implicated include the house dust mite (HDM) (e.g. Dermatophagoides pteronyssinus and Dermatophagoides farinaeae) and animal dander [4]. The pattern of rhinitis (seasonal or perennial) also depends by the climatic environment (temperate or tropical) [6].…”
Section: Introductionmentioning
confidence: 99%
“…AR is often considered as a mild disorder. It may be in fact regarded by parents as an irritation rather than as a significant disease and consequently to be ignored, underdiagnosed, misdiagnosed (with symptoms frequently attributed to a recurrent cold) and mistreated [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] Intranasal corticosteroids (INCs) are the most efficacious treatment option in relieving nasal congestion and controlling frequent symptoms and are the treatment of choice for persistent AR. 5,6 Nasacort (Sanofiaventis, Bridgewater, NJ; microcrystalline suspension of triamcinolone acetonide aqueous nasal spray [TAA-AQ]) has been marketed in the United States for nearly 2 decades and is approved for treating nasal symptoms of both perennial AR (PAR) and seasonal AR in adults and children. Double-blind, placebo-controlled studies have shown that TAA-AQ is effective and well tolerated in children.…”
Section: What This Study Addsmentioning
confidence: 99%